Forward drive : the race to build 'clean' cars for the future / Jim Motavalli. - Motavalli, Jim (Earthscan, 2001)
In this work on the future of the automobile, the author talks to the key players. He documents the actual and potential innovative changes that exist for clean, environmentally friendly vehicles.